Barium ions selectively activate BK channels via the Ca(2+)-bowl site - Zhou, Yu (National Academy of Sciences, 2012)
Activation of Ca(2+)-dependent BK channels is increased via binding of micromolar Ca(2+) to two distinct high-affinity sites per BK α-subunit. One site, termed the Ca(2+) bowl, is embedded within the second RCK domain (RCK2; regulator of conductance for potassium) of each α-subunit, while oxygen-containing residues in the first RCK domain (RCK1) have been linked to a separate Ca(2+) ligation site. Although both sites are activated by Ca(2+) and Sr(2+), Cd(2+) selectively favors activation via the RCK1 site. Divalent cations of larger ionic radius than Sr(2+) are thought to be ineffective at activating BK channels. Here we show that Ba(2+), better known as a blocker of K(+) channels, activates BK channels and that this effect arises exclusively from binding at the Ca(2+)-bowl site. Compared with previous estimates for Ca(2+) bowl–mediated activation by Ca(2+), the affinity of Ba(2+) to the Ca(2+) bowl is reduced about fivefold, and coupling of binding to activation is reduced from ∼3.6 for Ca(2+) to about ∼2.8 for Ba(2+). These results support the idea that ionic radius is an important determinant of selectivity differences among different divalent cations observed for each Ca(2+)-binding site.